2017
DOI: 10.4236/ojst.2017.79031
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ratios of Interleukin-1<i>β</i> and Intercellular Adhesion Molecule 1 in Gingival Crevicular Fluid after Scaling and Root Planing Associated with Periodontal Pocket Healing

Abstract: Objectives: Several researchers have investigated inflammatory cytokines in gingival crevicular fluid (GCF) from chronic periodontitis with clinical parameters after periodontal treatment. The aim of the present study was to identify the inflammatory cytokines present in GCF associated with periodontal pocket healing after scaling and root planing (SRP). Methods: Twenty patients were enrolled, and clinical examinations including probing pocket depth (PPD) and bleeding on probing (BOP) were performed at the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…Although bleeding on probing (BOP) is a classical and beneficial indicator of periodontitis progression [ 19 , 20 ], it cannot distinguish between minute and massive bleeding and is not quantitative. Recently, inflammatory cytokines in gingival crevicular fluid (GCF), such as MMP-8, IL-1, and TNF-α, were measured and found to be associated with disease progression and response to treatment [ 21 , 22 , 23 ]. However, the measurement of these cytokines is performed by ELISA, which is expensive in terms of purchasing equipment and testing costs.…”
Section: Discussionmentioning
confidence: 99%
“…Although bleeding on probing (BOP) is a classical and beneficial indicator of periodontitis progression [ 19 , 20 ], it cannot distinguish between minute and massive bleeding and is not quantitative. Recently, inflammatory cytokines in gingival crevicular fluid (GCF), such as MMP-8, IL-1, and TNF-α, were measured and found to be associated with disease progression and response to treatment [ 21 , 22 , 23 ]. However, the measurement of these cytokines is performed by ELISA, which is expensive in terms of purchasing equipment and testing costs.…”
Section: Discussionmentioning
confidence: 99%
“…La relación entre los valores de los parámetros clínicos con los niveles de IL-1α e IL-1β, mostró una correlación significativa, que no se observó con el TNF-α, estos resultados son similares a los obtenidos por otras investigaciones que reportan una mayor concentración de mediadores en tejido inflamado, y en relación directa con los parámetros periodontales [30][31][32][33] . Por el contrario, otros estudios no han mostrado correlaciones entre los parámetros clínicos periodontales y los mediadores de la inflamación estudiados 21,26,34 .…”
Section: Discussionunclassified
“…The present authors previously used a membrane antibody array to measure levels of multiple cytokines in GCF from patients with chronic periodontitis before and after scaling and root planing (SRP). The findings suggested that IL-1β in GCF is related to periodontal healing [14].…”
Section: Introductionmentioning
confidence: 89%